Preparation and Audit of Consolidated Statements in Belarus: Status, Problems, Prospects - Korotaev, Sergey (Buhalterinės apskaitos teorija ir praktika, 2018)
[full article, abstract in English]The study purpose is development of a methodology for preparation of consolidated financial statements in the context of harmonization of the national system of accounting and preparation of statements with IFRS norms and principles. Study objectives: a) analysis of normative legal acts governing the preparation of consolidated financial statements in Belarus; b) identification of problematic issues arising during preparation of consolidated financial statements in accordance with the national legislation; c) development of specific proposals for improving the methodology for preparation of consolidated statements; d) analysis of the practice of audit of consolidated financial statements prepared in accordance with the national legislation and IFRS. In order to achieve tasks assigned, the author analyzes national normative legal acts that regulate the preparation of consolidated financial statements, examines specific consolidation mechanisms that raise questions among authors of statements, identifies approaches to resolving problematic consolidation issues, identifies reasons that prevent the preparation of reliable statements, as well as reasons for their non-preparation. Investigation of issues related to preparation of consolidated statements is linked to problematic issues of audit of such statements. The conclusion includes proposals for improvement of organization and clarification of the methodology for preparation of consolidated statements, as well as proposals for amending the legislation on audit activities on issues related to the audit of consolidated accounting statements.
Keywords: consolidated statements, preparation of statements, consolidation corrections, intra-group transactions, unrealized income, deferred tax assets, audit of statements